An extensible and scalable cloud information monitoring middleware. (24th April 2020) - Xiao, Peng
With the increasing complexity of cloud systems, how to efficiently manage cloud infrastructures has become a challenging task, while an effective monitoring service plays a crucial role to achieve this goal. In this paper, we present an extensible and scalable cloud monitoring middleware called extensible cloud monitoring service (ECMS), which is designed for offering online monitoring service to different monitoring requests from either cloud users or resource providers. In ECMS, a layered monitoring framework is introduced with aiming to cover different aspects of cloud monitoring requests. The implementation of ECMS is evaluated in a real-world cloud test-bed and the results indicate that it can efficiently provide online monitoring services to different kinds of clients and exhibits better scalability and robustness comparing with other monitoring systems.